Interaction model of employee’s personality traits, subjectively evaluated transformational leadership, work motivation and organizational commitment - Genevičiūtė-Janonienė, Giedrė; Endriulaitienė, Auksė (Psichologija, 2010)
Organizational commitment and work motivation are important research topics having both teoretical and empirical implication for a long time because of their potential prediction of absenteeism, intention to leave or turnover, job satisfaction, job performance or even productivity (Randall, 1990; Amabile, 1993; Lee et al., 2001; Cetin, 2006; Kuvaas, 2006). Especially it is a very important topic for supervisors traying to survive this economic crisis. Some of researchers noticed work motivation and organizational commitment to be very effective cure for this crisis (Pollard and Hotho, 2006; Selmer and Waldstrom, 2007; Leidl, 2009). The research has been targeted to define the employee’s personality traits and subjectively evaluated transformative leadership correlations with work motivation and organizational commitment and to produce an interaction model of variables. The research involved 462 Lithuanian employees representing different size and type organizations. The results showed that high level of extraversion (r = 0.242; p < 0.001), agreeableness (r = 0.206; p < 0.001) or conscientiousness (r = 0.300; p < 0.001) result in greater degree of work motivation. And the greater degree of neuroticism evokes less work motivation in women (r = –0.252; p < 0.001). However, neuroticism in male respondents is not related to work motivation (p > 0.05). Moreover, the greater degrees of conscientiousness (r = 0.221; p < 0.001) or agreeableness (r = 0.250; p < 0.001) result in higher organizational commitment. Male respondents with higher extraversion are more committed (r = 0.319; p < 0.01), but extraversion in women is not related to organizational commitment (p < 0.07). The increase of neuroticism in women weakens their organizational commitment (r = –0.217; p < 0.01). However, neuroticism in male respondents is not related to organizational commitment (p > 0.05). Moreover, higher degree of transformational leadership promotes work motivation degree (r = 0.384; p < 0.001) and greater organizational commitment (r = 0.574; p < 0.001) in employees. Also the results showed that increasing work motivation increases organizational commitment (r = 0.609; p < 0.001). And finally, agreeableness directly influences both organizational commitment and work motivation in men, whereas extraversion has significant influence on men’s organizational commitment and conscientiousness has significant influence on women’s organizational commitment through mediating variable i.e. work motivation. Transformational leadership has direct impact on both work motivation and organizational commitment.